Stabilization and Incipient Carbonization of Electrospun Polyacrylonitrile Nanofibers Fixated on Aluminum Substrates - Jan Lukas Storck (Fibers, 2020)
Polyacrylonitrile (PAN) nanofibers, prepared by electrospinning, are often used as a precursor for carbon nanofibers. The thermal carbonization process necessitates a preceding oxidative stabilization, which is usually performed thermally, i.e., by carefully heating the electrospun nanofibers in an oven. One of the typical problems occurring during this process is a strong deformation of the fiber morphologies—the fibers become thicker and shorter, and show partly undesired conglutinations. This problem can be solved by stretching the nanofiber mat during thermal treatment, which, on the other hand, can lead to breakage of the nanofiber mat. In a previous study, we have shown that the electrospinning of PAN on aluminum foils and the subsequent stabilization of this substrate is a simple method for retaining the fiber morphology without breaking the nanofiber mat. Here, we report on the impact of different aluminum foils on the physical and chemical properties of stabilized PAN nanofibers mats, and on the following incipient carbonization process at a temperature of max. 600 °C, i.e., below the melting temperature of aluminum.